The Digitalization Influence on the Transformation of Public Administration Methodology - V. V. Zotov; L. A. Vasilenko (Управленческое консультирование)
The article shows that the ongoing processes of networkization, digitalization and hybridization lead to the creation of such a sociotechnical phenomenon as information and analytical platforms, which actualize a new type of social network relations between authorities and citizens in the public space of communications. In these conditions, a new methodology of public administration is required, which would take into account the digital realities of the modern world. According to the authors, the new concept of public administration should be built taking into account the development of a methodology for the following mutually conditioned processes: 1) creation of information and analytical platforms of the digital society; 2) formation of social structures in the network space; 3) configuration of relational networks for solving socially significant problems. It should be based on the actor-network concept and the digitalization ethics, the social network analysis, the relational sociology, the concept of figuration, the fractal-evolutionary concept, the concept of configuring a relational network of stakeholders.